Comparison of Incidence of Urinary Tract Infection in Diabetic vs Non-Diabetic and Associated Pathogens - Ramrakhia, Sonam (Cureus, 2020)
Introduction Urinary tract infections (UTIs) are common in low socioeconomic country like Pakistan. There are various factors responsible for UTI, one major factor being diabetes. This study aims to compare diabetic and non-diabetic patients, for gender association, symptoms, and organisms, with UTI. Methods  This cross-sectional study was conducted in the medicine ward of tertiary care hospital in Pakistan from January 2019 to December 2019. For urine analysis, freshly voided 5-10 ml of clean midstream urine specimens was collected in a sterile container. Samples were sent to the lab immediately, A colony count of ≥10(5 )CFU/ml was considered for the diagnosis of UTI. Culture was done if UTI was diagnosed. Results  The overall incidence of UTI in participants of the diabetic group was significantly higher than those in the non-diabetic group (13.67% vs 6.40%; P=0.004). Escherichia coli was the most common organism in both the diabetic and non-diabetic groups (60% vs 72%; P=0.73). Frequency of Klebsiella was considerably higher in the participants of diabetes but it was not significant (23.3% vs 11.1%; P=0.29). Conclusion  UTI was significantly higher in the diabetic population compared to the non-diabetic population. Since diabetes is prevalent in Pakistan, care of diabetes should include reducing the risk factors for UTI.